2010
DOI: 10.1186/1476-069x-9-64
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical responses in healthy cyclists briefly exposed to traffic-related air pollution: an intervention study

Abstract: BackgroundNumerous epidemiological studies have demonstrated adverse health effects of a sedentary life style, on the one hand, and of acute and chronic exposure to traffic-related air pollution, on the other. Because physical exercise augments the amount of inhaled pollutants, it is not clear whether cycling to work in a polluted urban environment should be encouraged or not. To address this conundrum we investigated if a bicycle journey along a busy commuting road would induce changes in biomarkers of pulmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
77
5
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(94 citation statements)
references
References 45 publications
9
77
5
1
Order By: Relevance
“…Studies of acute (20 minutes to 2 hours) effects of real-life traffic exposure on healthy volunteers have been unremarkable and are limited to a small increase in the percentage of blood neutrophils (Jacobs et al, 2010), modest effects on peak flow, exhaled nitric oxide and airway resistance (Zuurbier et al, 2011a, b). A study by Strak et al (2012) was specifically designed to evaluate the contribution of different pollutants.…”
Section: Rationalementioning
confidence: 99%
“…Studies of acute (20 minutes to 2 hours) effects of real-life traffic exposure on healthy volunteers have been unremarkable and are limited to a small increase in the percentage of blood neutrophils (Jacobs et al, 2010), modest effects on peak flow, exhaled nitric oxide and airway resistance (Zuurbier et al, 2011a, b). A study by Strak et al (2012) was specifically designed to evaluate the contribution of different pollutants.…”
Section: Rationalementioning
confidence: 99%
“…Kumar et al (2011a) have shown significant contributions to excess mortality due to the exposure to traffic-derived UFP in urban areas. Jacobs et al (2010) and Bos et al (2011) have shown that even brief exposure of healthy people to traffic UFP seems to induce some health effects. Moreover, those particles may also cause cardio-vascular damage (de Hartog et al, 2003) and could cause brain stroke when penetrating into the bloodstream and being transported to other organs (Hong et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Nitric oxide is conveyed by different cell types in the respiratory tract including epithelial cells, macrophages, neutrophils, mast cells and vascular endothelial cells (Ricciardolo, 2003;Jacobs et al, 2010). A number of demographic, anthropometric and biological factors (such as age, gender, height, smoking, infection and allergy), reviewed by Abba (2009), can affect the eNO concentration levels.…”
Section: Introductionmentioning
confidence: 99%